Identification of the psychological and behavioral conditions of cats from owners' perspective during the COVID-19 pandemic in Türkiye - Ozturk, Yahya; Erten, Omer; Seker, Ibrahim; Koseman, Abdurrahman (Univ Cordoba, 2025)
Objective. This study aims to examine the psychological and behavioral status of domestic cats (Felis catus) during the COVID-19 pandemic. Materials and methods. Study's material included the data collected from the responses of 306 cat owners who participated in the survey voluntarily. Results. During the study, 36.9% of the participating cat owners reported that their cats had some abnormal behaviors besides their normal behaviors during the pandemic. The most frequently mentioned abnormal behaviors were increased meowing (38.8%) and a greater desire for close contact (38.8%). Furthermore, 4.4% of cat owners said that their cats had abnormal behaviors like not using the litter box and urinating everywhere. Conclusions. As a result, the majority of cat owners who have participated in this study stated that there was no significant change in the mood and behavior of their cats during the COVID-19 pandemic, that it was beneficial to be a cat owner, and that they did not face many difficulties in taking care of their cats. Pets, with whom people spent more time during the pandemic, should be monitored in terms of animal welfare after the pandemic. Providing pet owners with information on special animal welfare would be beneficial in understanding the changes in human-animal interactions in similar pandemics and managing this process effectively.
Identificación de las condiciones psicológicas y conductuales de los gatos desde la perspectiva de los propietarios de gatos durante la pandemia de COVID-19 en Turkia
Keywords: COVID-19 pandemic; emotional health; human-cat interactions; cats (Source: MeSH)